Women's Empowerment Based on Digital Financial Skills - Rafidah; Rosmanidar, Elyanti; Anita, Efni; Mutia, Agustina; Kusnadi, Dedek; Fusfita, Nurlia; Rahma, Sri; Permata, Tika Agu; Husen, Muhammad; Andriana, Nirhamni; Yuniar, Vita (PT Inovasi Pratama Internasional, 2023)
Achieving gender equality and economic independence. These programs aim to increase women's access to financial services, promote entrepreneurship, and facilitate economic participation through the use of digital technology. By providing training in personal financial management, e-commerce, and online banking applications, women can overcome traditional barriers such as limited access and cultural norms that limit their financial inclusion. This research explores the transformational potential of these empowerment programs, highlighting the importance of cross-sector collaboration and supporting policies to achieve the full potential of women's empowerment through digital financial skills.